Educators in Improving Generation Z’s Understanding of Islamic Family Law and Strengthening Institutional Legality and Governance Towards Independence and Compliance with the Law: A Seminar Study at MI Nurul Falah Cisauk and Ponpes Sirojul Adhfal Cisoka - Hendri Supriyanto; Miftahul Hadi (International Research and Development for Human Beings (IRDH), 2025)
This study examines the role of educators in improving Generation Z's understanding of Islamic family law and strengthening the legality and governance of educational institutions towards independence and legal compliance in Tangerang Regency. This activity was conducted through two seminars held at the MI Nurul Falah Cisauk Foundation with 23 teachers and principals as participants, and at the Sirojul Adhfal Cisoka Islamic Boarding School with 93 students. The research method used was descriptive qualitative with in-depth data analysis. The results indicate that educators have a strategic role as agents of change in delivering Islamic family law material effectively, with an approach that suits the characteristics of Generation Z. In addition, the legality and good institutional governance are important foundations in supporting the sustainability and quality of education. This study recommends strengthening the capacity of educators and institutional governance as a crucial step in shaping a Generation Z who is legally aware and adheres to the values of Islamic family law.